2022
DOI: 10.1021/acs.cgd.2c00569
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Morphological Regulation Mechanism of Low Sensitivity and Highly Energetic Materials in Solvents: Changing Crystal Morphology Induced by Hydrogen Bonding

Abstract: Low sensitivity and highly energetic materials (LSHEMs) are currently the most promising high-energy materials due to their structural stability. However, many problems exist due to their abundant hydrogen bonding (HB) in the structure, such as low solubility and difficulty controlling the crystallization process. In this paper, aiming at regulating the crystal morphology of LSHEMs, 4,4′,5,5′-tetranitro-1H,1′H-[2,2′-biimidazole]-1,1′-diamine is used as a model substance to explore the mechanism of controlling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In recent years, the application of morphology prediction models, such as the MAE models, , growth mechanistic model, , and dynamic Monte Carlo simulation method, has become increasing popular. Morphology prediction models have been also widely applied in energetic crystals grown under various conditions, such as vacuum, solvents, and additives, with effects of temperature, volume ratio of mixed solvents, supersaturation, and other conditions covered. Also, this research revealed the growth mechanism of energetic crystals at the microscopic level, which presented theoretical guidance for morphology control. Meanwhile, valid force fields are important for the specified energetic compounds.…”
Section: Application Of Morphology Prediction Methods In Energetic Cr...mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the application of morphology prediction models, such as the MAE models, , growth mechanistic model, , and dynamic Monte Carlo simulation method, has become increasing popular. Morphology prediction models have been also widely applied in energetic crystals grown under various conditions, such as vacuum, solvents, and additives, with effects of temperature, volume ratio of mixed solvents, supersaturation, and other conditions covered. Also, this research revealed the growth mechanism of energetic crystals at the microscopic level, which presented theoretical guidance for morphology control. Meanwhile, valid force fields are important for the specified energetic compounds.…”
Section: Application Of Morphology Prediction Methods In Energetic Cr...mentioning
confidence: 99%
“…Still, the characteristics of the component and packing structure of a crystal face are widely adopted to understand a crystal growth mechanism and to guide the selections of solvent and modifier. For example, Liu et al considered the packing structure of a crystal face to accurately predict the morphology of some energetic crystals, , and Wang et al adopted the hydrogen bonding density to uncover the morphological regulation mechanism of low sensitivity and highly energetic materials in solvents . Besides, the crystal packing structure is considered in all the aforementioned models, showing its importance therein.…”
Section: Morphology Engineering Of Energetic Crystalsmentioning
confidence: 99%
“…Among these exposed crystal faces, the (0 −2 0) and (0 2 0) faces have the minimum absolute adhesion energy (−95.24 Hirshfeld surface (HS) analysis [34][35][36][37] has been used to investigate intermolecular interactions, and could directly discern the intermolecular interaction sites in a crystal. 38,39 The Hirshfeld surface of the rifampicin molecule is displayed in Fig. 5(a), where the red and blue stand for high and low close contact populations, respectively.…”
Section: Characterizationmentioning
confidence: 99%
“…Following its synthesis by Breiner’s group in 2013, DATNBI has been noted for its excellent explosive performance and safety, and its crystal structures have been progressively uncovered in recent years. Currently, form α and form β are the discovered polymorphs of DATNBI, with form α identified as a rare polymorph in extensive experiments. , Moreover, many studies found that the dimer structures are relevant to nuclei structure and affect the polymorphism. In our previous research, the existence of hydrogen bonding dimers of DATNBI in solution was demonstrated using DFT and infrared spectroscopy and was found to play a decisive role in the DATNBI solid forms . Therefore, we hypothesized that the shape of the dimer assembly may be a good model for the polymorph selection.…”
Section: Introductionmentioning
confidence: 96%
“…Currently, form α 30 and form β 31 are the discovered polymorphs of DATNBI, with form α identified as a rare polymorph in extensive experiments. 32,33 Moreover, many studies found that the dimer structures are relevant to nuclei structure and affect the polymorphism. 34−36 In our previous research, the existence of hydrogen bonding dimers of DATNBI in solution was demonstrated using DFT and infrared spectroscopy and was found to play a decisive role in the DATNBI solid forms.…”
Section: Introductionmentioning
confidence: 99%